Avaliação do comportamento mecânico de misturas asfálticas produzidas com ligantes asfálticos modificados por ácido polifosfórico e aditivos poliméricos, enfatizando a resistência à deformação permanente - Onofre, Felipe Coutinho (2012)
Asphalt binders modification is a common practice in heavy traffic roadways and its goal is to improve binder’s rheological properties, especially in extreme temperatures. The main objective of this research was to evaluate the mechanical behavior of mixes designed with asphalt binders modified with polyphosphoric acid and polymers, with respect to their stiffness and rutting resistance. Seventeen asphalt mixes with two types of aggregate with the same gradation, but with asphalt binder modified by different types of polymer, ground tire rubber and polyphosphoric acid (PPA) were investigated. Repeated load permanent deformation test was used to evaluate the asphalt mixes’ rutting resistance, and the dynamic modulus test results were used to characterize asphalt mixes stiffness. The results showed that asphalt binder modification influenced substantially the asphalt mixes rutting resistance, especially those with polymer+PPA modified binder, which did not reach Flow Number value (failure criteria for the repeated load permanent deformation test). Asphalt binder modification also increased the stiffness for all asphalt mixes evaluated in this study. For low frequency loading the stiffness variation was higher when compared to the high frequency ones. PPA proved to be a modifier that increases asphalt mixes stiffness and rutting resistance. Also it can be considered as an important tool for the polymer economy, since its use dispensed a high polymer content for asphalt binder modification. It was also verified for the asphalt mixes investigated that there are no correlations between asphalt binder characterization and rutting resistance parameters for the asphalt mixes. Finally, the analysis performed for the asphalt mixes with the same type of aggregate, but with different types of asphalt binder, and for the asphalt mixes with the same asphalt binder but with different aggregate type, showed that the asphalt mixes’ rutting resistance is much more influenced by the aggregate type than by the asphalt binder.